Paris Texas - Wim Wenders; Bernhard, Berry; Clément Claresie; Mobley Hunter Carson; Stanton Sam; Stockwell Aurore; Wicki Dean; Harry Dean (France Road Movies Filmproduktion, 1984)
A man wanders out of the desert not knowing who he is. His brother finds him, and helps to pull his memory back of the life he led before he walked out on his wife and son four years before. As his memory returns, he makes contact with various people from his past.
A man wanders out of the desert not knowing who he is. His brother finds him, and helps to pull his...
L.M. Kit Carson
Language(s): English, Turkish, German Subtitle(s): Turkish
Keywords: Drama